The Business Politics of Chinese Ethnic in Bangka Belitung on Post New Order Era - IBRAHIM, IBRAHIM (Universitas Muhammadiyah Yogyakarta, 2015)
Since the reformation era, Chinese ethnic are in distinctive situation near to all line. Before New Order Era, Chinese et hnic was accustomed to business sector. On post New Order Era, that ethnic have dawned on the same importance position within all have been around maintenance character with wide variety. Whether the previous pattern of capitalists evolved into the main feature, this situation has been penetrative on post new order era. The article aims to outline the Chinese business politics in Bangka Belitung on post New Order Era. Using the qualitative methods with elite approaches, this article found that there was a political expansion of Chinese businesses in Bangka Belitung when New Order Era expired. The expansion of collusion through elite and politicians, the reinforcement of identity and accessory networking, the more disguised expansion of new business units, and decentralized business networking are the dependent character of Chinese business political practices, nowadays.KEYWORDS: Politics, Business, Ethnic, Chinese